The impact COVID-19 pandemic on coverage and inequalities in childhood immunization in Peru - Larissa A N Silva; Francine S Costa; Bianca O Cata-Preta; Luis Huicho; Claudio F Lanata; Maria Ana Mendoza Araujo; Theresa J Ochoa; Tewodaj Mengistu; Dan Hogan; Aluisio J D Barros; Cesar G Victora (International Journal for Equity in Health)
Abstract Background We examined the impact of COVID-19 on childhood immunization coverage and inequalities in Peru, focusing on pentavalent, rotavirus, and pneumococcal (PCV) vaccines. Since the 1990s, Peru has worked to improve childhood vaccine coverage, but the COVID-19 pandemic posed significant challenges to the health system. Methods We analysed data from nationally representative health surveys conducted annually between 2015 and 2023. The surveys measured vaccine coverage among children aged 18–29 months, namely three doses for pentavalent and PCV and two doses for the rotavirus vaccine, based on data from home-based records. We studied inequalities at the individual child level using the slope index of inequality (SII) based on household wealth quintiles. Results In 2019, the home-based record coverage levels for pentavalent, PCV and rotavirus vaccines were 78.0%, 74.5%, and 75.9%, respectively. In 2020, these rates dropped significantly due to pandemic disruptions: PCV and pentavalent coverage fell by 14% points, and rotavirus by 12 points. By 2021, coverage levels improved, returning to pre-pandemic rates by 2022 and 2023. Individual-level analyses showed that pro-rich inequalities were present during the full study period, but these increased sharply during the pandemic in 2020, with poorer children experiencing more significant drops in coverage than wealthier children. This trend reversed by 2021 and 2022 when inequality measures returned to pre-pandemic levels. Due to reasons that are still unclear, inequality increased again in 2023. Nevertheless, the confidence intervals for the summary inequality measures are wide and must be interpreted cautiously. Conclusions The COVID-19 pandemic temporarily disrupted Peru’s childhood immunization efforts, particularly affecting poorer populations, but coverage rebounded to pre-pandemic levels by 2022. These findings contribute to the scant literature on the pandemic’s impact on vaccine equity.